Courseware : English comprehension for Year 1 KBSR using 3D approach / Lindzia Azreen Azmi - Azmi, Lindzia Azreen (2005)
The English Comprehension for Year 1 KBSR prototype courseware is developed through the combination of visualization 3D and interactive 3D element where it uses three-dimensional character animation and objects. The reason of developing this courseware is to bring a new dimension of approach in teaching and learning English Comprehension for Year 1. This report discusses the implementation and the findings of English Comprehension for Year 1 using 3D as a new approach in interactive multimedia. Systematic methods based on multimedia framework- have been chosen to implement multimedia 3D relating to this system. In addition, a powerful computer system together with the appropriate 3D authoring tools is identified in order to fulfill this system prototype requirement.